CD105 as a tool for assessing microvessel density in renal cell carcinoma - Cioca, Andreea; Muntean, Diana; Bungardean, Catalina (Indian journal of pathology & microbiology, 2019)
Background: Angiogenesis plays an essential role in both tumor growth and metastasis. CD105 expression was correlated with prognosis in many tumors, but its value in renal cell carcinoma (RCC) is still questionable. Materials and Methods: The aim of this study was to evaluate microvessel density (MVD) by using CD105 marker, in 95 cases of renal cell carcinoma. Results: CD105 showed positivity in 93 cases. The mean MVD value was significantly higher in clear cell carcinoma compared to papillary and chromophobe subtypes (P = 0.000). We noticed a significant correlation between MVD and ISUP grade (P = 0.007). The highest MVD value was observed in tumors with ISUP grade 1 and 2, while the lowest MVD value was noted in ISUP grade 3 tumors. A high vessel density was identified in tumors with a low Fuhrman grade, compared to those with a high grade (P = 0.010). MVD value was lower in tumors with a larger diameter, compared to small ones (P = 0.026). Conclusion: In conclusion, CD105 expression (MVD) is inversely related to tumor aggressiveness in clear cell RCC and can be used as a favorable prognosis marker. The vascularity differences between histological subtypes of RCCs could be useful for a better selection of patients that may benefit from anti-angiogenic therapies.